Second law analysis of a spark ignition engine under high values of ignition retard. (1st January 2012) - Ozcan, Hakan; Özbey, Mustafa; Söylemez, M. Sait; Topaloglu, Bahattin
The availability analysis of an Spark-Ignition (SI) engine under High Values Ignition Retard (HVIR) was investigated. Liquefied Petroleum Gas (LPG) was used as fuel. The results obtained in this paper may provide guidance to determine the proper ignition retard timing for cold-start emissions control. Results showed that cylinder pressure, availability transfer by heat and availability transfer by work significantly decreased as the spark timing was changed from normal to most retarded timing. Finally, as the spark timing was changed from normal timing to the most retarded timing, the availability transfer due to net exhaust flow and availability destruction due to combustion were significantly increased.